Aqueously Cathodic Deposition of ZIF‐8 Membranes for Superior Propylene/Propane Separation. (6th November 2019) - Wei, Ruicong; Chi, Heng‐Yu; Li, Xiang; Lu, Dongwei; Wan, Yi; Yang, Chih‐Wen; Lai, Zhiping
Abstract: Electrochemical deposition has emerged as a novel approach to fabricate metal–organic framework (MOF) films. Here, for the first time, an aqueously cathodic deposition (ACD) approach is developed to fabricate ZIF‐8 type of MOF membranes without addition of any supporting electrolyte or modulator. The fabrication process uses 100% water as the sole solvent and a low‐defect density membrane is obtained in only 60 min under room temperature without any pre‐synthesis treatment. The membrane exhibits superior performance in C3 H6 /C3 H8 separation with 182 GPU C3 H6 permeance and 142 selectivity, making it sit at the upper bound of permeance versus selectivity graph, outperforming majority of the published data up to 2019. Notably, this approach uses an extremely low current density (0.13 mA cm −2 ) operated under an ultrafacile apparatus set‐up, enabling an attractive way for environmentally friendly, energy efficient, and easily scalable MOF membrane fabrications. This work demonstrates a great potential of aqueously electrochemical deposition of MOF membrane in the future research. Abstract : An ultrathin ZIF‐8 membrane with ≈ 500 nm thickness is fabricated via a novel aqueous cathodic deposition method. The membrane shows superior C3 H6 /C3 H8 separation performance with the permeance of C3 H6 up to 182 GPU and a selectivity of C3 H6 over C3 H8 up to 142, which surpasses all the reported membrane performances prepared by conventional methods.